2019
DOI: 10.1055/s-0039-1688412
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thrombosis in Children with Acute Lymphoblastic Leukemia Treated on DCOG ALL-9 and ALL-10 Protocols: The Effect of Fresh Frozen Plasma

Abstract: Background Venous thromboembolism (VTE) is an important complication for treatment of acute lymphoblastic leukemia (ALL) in children. Especially, ALL treatment, with therapeutics such as asparaginase and steroids, increases the thrombotic risk by reduction in procoagulant and anticoagulant proteins. Replacement of deficient natural anticoagulants by administration of fresh frozen plasma (FFP) may have a preventive effect on the occurrence of VTE. Methods We retrospectively analyzed all consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Adult studies showed that prophylactic anticoagulation could be safely administered without increasing the number or severity of bleeding events, resulting in a reduction in VTE’s cumulative incidence [ 24 ] in ALL patients. Hence, VTE prophylaxis [ 25 ] or protein replacement with fresh frozen plasma [ 26 ] has recently been proposed in patients with ALL during the induction period with pediatric clinical trials ongoing. In our study, prophylactic anticoagulation in ALL was not employed.…”
Section: Resultsmentioning
confidence: 99%
“…Adult studies showed that prophylactic anticoagulation could be safely administered without increasing the number or severity of bleeding events, resulting in a reduction in VTE’s cumulative incidence [ 24 ] in ALL patients. Hence, VTE prophylaxis [ 25 ] or protein replacement with fresh frozen plasma [ 26 ] has recently been proposed in patients with ALL during the induction period with pediatric clinical trials ongoing. In our study, prophylactic anticoagulation in ALL was not employed.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, it has been reported that treatment with LMWH for a minimum of 3 months and until L‐asparaginase therapy is over with major radiologic improvement seems to be effective and feasible 31 . It is thought to have a positive prophylactic effect 32 . New oral anticoagulants (NOACs) such as rivaroxaban can be used in some thromboembolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…31 It is thought to have a positive prophylactic effect. 32 New oral anticoagulants (NOACs) such as rivaroxaban can be used in some thromboembolic disorders. Results of the EINSTEIN-Jr CVT study showed that rivaroxaban is effective and safe in pediatric CVT.…”
Section: Discussionmentioning
confidence: 99%
“…Adult studies showed that prophylactic anticoagulation could be safely administered without increasing the number or severity of bleeding events, resulting in a reduction in the cumulative incidence of VTE(24) in ALL patients. Hence, VTE prophylaxis(25) or protein replacement with fresh frozen plasma(26) has recently been proposed in patients with ALL during the induction period with pediatric clinical trials ongoing. In our study, prophylactic anticoagulation in ALL was not employed.…”
Section: Discussionmentioning
confidence: 99%